From vulnerability to leadership: How small island developing states are pioneering climate-health adaptation strategies - A systematic review - Abeng, Andi Tenri; Amiruddin, Ridwan; Birawida, Agus Bintara; Salam, Abdul; Ibnu, Indra Fajarwati; Farhum, Aisyah; Sari, Uswatun Hasanah Purnama (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Climate change represents one of the most significant public health challenges of the 21st century, with Small Island Developing States (SIDS) experiencing disproportionate impacts. Traditional discourse has positioned SIDS as vulnerable victims; however, emerging evidence suggests that they are pioneering innovative climate-health adaptation strategies. Methods: A systematic search of PubMed, Embase, Web of Science, and grey literature databases (2010-2024) following the PRISMA guidelines. Studies from officially recognized SIDS focusing on climate-health adaptation and leadership were included. Data were synthesized thematically to identify leadership models, governance approaches and measurable outcomes. Results: Of 2,847 records, 67 studies from 34 SIDS met the inclusion criteria. Five leadership themes emerged: community-based governance (n=45), traditional knowledge integration (n=38), regional collaboration (n=31), adaptive health systems (n=29), and Indigenous innovation (n=22). SIDS demonstrated significant leadership by establishing regional climate-health surveillance networks, pioneering nature-based health interventions, and creating community-led early warning systems, achieving a 78% average hazard detection improvement. Discussion: SIDS have evolved into climate-health adaptation leaders through innovative governance models that integrate traditional knowledge, community participation, and regional cooperation. Their leadership provides valuable lessons for global climate-health adaptation, demonstrating that small size and resource limitations can catalyze rather than constrain innovation.